How Far Has the Development of Endometriosis Murine Models Progressed? A Systematic Review - Hermawan, Wibisono; Ayu Rizky, Widowati; Leny Silviana , Farida (Jurnal Kedokteran Brawijaya, 2026)
Up to 15% of women of reproductive age suffer with endometriosis, an inflammatory condition that is dependent on estrogen. Its complex nature and nonspecific symptoms often delay diagnosis and treatment. Due to limited human studies and rare spontaneous cases in primates, murine models are essential for exploring disease mechanisms and therapies. This systematic review evaluated seven experimental studies conducted between 2005 and 2025 using murine models, selected from PubMed, Cochrane, SCOPUS, and Taylor & Francis databases. Most studies employed syngeneic models, which facilitate compatibility with transgenic tools. Advanced visualization techniques, such as GFP fluorescence and luciferase-based bioluminescence, allowed non-invasive and real-time tracking of lesion development. Although these models offer significant advantages, inconsistencies in hormonal protocols, tissue sources, and imaging depth remain challenges. Despite these limitations, murine models have progressed notably, particularly with innovative imaging technologies. However, further standardization and improvements in physiological relevance are needed to enhance translational potential.